Peningkatan Efisiensi Kerja Dengan Penerapan Digital Standard Operating Procedure (SOP) Pada Proses Manufaktur (Studi Kasus: Mesin Bubut Konvensional) - Irvando Anto Verry Damanik (Jurnal POLIMESIN, 2022)
The development of the use of digital-based technology has become a challenge as well as an opportunity in Industry 4.0 era, especially in the manufacturing industry. The machining process is one of the important and dominant part in the implementation of the manufacturing industry, so it is necessary to find a way to get the expected results with time efficiency in the process because it will be a factor that determines the total operating costs incurred. To optimize all used resources and minimize engine idle time, the Digital Standard Operating Procedure (DSOP) method is a solution. DSOP is one step in digital transformation in order to optimize guidelines for the implementation of the machining process which also replaces working papers as operator guidance on the production floor. The method is used to compare the time required by the operator in carrying out the machining process using the DSOP with the old method. From the day of observation, it was found that there was a time saving of up to 50% by the operator, compared to conventional machining process methods. Digital SOP also provides a more communicative guide accompanied by complete pictures of the products made, as well as videos on how to set-up tools and workpieces on machines. With the use of digital-based SOPs, the time required for operators is shortened and SOP is understood more accurately from planning, monitoring until implementing, which are presented digitally